2006
DOI: 10.1016/j.jaap.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-structural changes during the thermal treatment of hydrogen-rich vitrinites caused by the presence of terpene-type resin

Abstract: The vitrain from Teruel (North-Eastern Spain) is a good example of a vitrinite whose perhydrous character and anomalous properties are caused by the presence of terpene-type resin. The sample used in this work was isothermally pyrolysed in an open-medium system at temperatures ranging from 250 to 500 °C. A mass balance, a petrographic and geochemical characterisation of the pyrolysates and compositional and structural analyses (GC and NMR) of the generated oils were performed. The results confirm the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Although the influence of liptinite and inertinite on the chemistry of adjacent macerals has been addressed in several studies (Hutton & Cook, 1980; Mastalerz et al , 1993a, b; Suárez‐Ruiz et al , 1994; Stankiewicz et al , 1996; Iglesias et al , 2006), no consensus has been reached about underlying mechanisms. Three possible causes have been suggested to explain alterations of vitrinite's chemistry in the proximity of liptinite and inertinite macerals: (1) botanic precursors and the depositional environment; (2) coalification history of particular samples and (3) intermaceral reactions during the early peat‐forming stage or during later coalification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the influence of liptinite and inertinite on the chemistry of adjacent macerals has been addressed in several studies (Hutton & Cook, 1980; Mastalerz et al , 1993a, b; Suárez‐Ruiz et al , 1994; Stankiewicz et al , 1996; Iglesias et al , 2006), no consensus has been reached about underlying mechanisms. Three possible causes have been suggested to explain alterations of vitrinite's chemistry in the proximity of liptinite and inertinite macerals: (1) botanic precursors and the depositional environment; (2) coalification history of particular samples and (3) intermaceral reactions during the early peat‐forming stage or during later coalification.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that the associated liptinite (i.e. resinite, alginite) and inertinite macerals are likely to influence the chemical properties of vitrinite (Hutton & Cook, 1980; Mastalerz et al , 1993a, b; Suárez‐Ruiz et al , 1994; Stankiewicz et al , 1996; Iglesias et al , 2006). However, there is still no consensus on the reasons leading to the variation of vitrinite's chemistry.…”
Section: Introductionmentioning
confidence: 99%